ChemInform Abstract: Efficient Domino Hydroformylation/Benzoin Condensation: Highly Selective Synthesis of α‐Hydroxy Ketones. Issue 17 (April 2016) - Dong, Kaiwu; Sang, Rui; Soule, Jean‐Francois; Bruneau, Christian; Franke, Robert; Jackstell, Ralf; Beller, Matthias
Abstract: Olefins are smoothly and with excellent regioselectivity converted into the corresponding α‐hydroxy ketones using a specific catalytic system consisting of a rhodium/phosphine complex and the CO2 adduct of a N‐heterocyclic carbene.